Self-medication with over the counter drugs, prevalence of risky practice and its associated factors in pharmacy outlets of Asmara, Eritrea - Sirak Tesfamariam; Indermeet Singh Anand; Ghide Kaleab; Samson Berhane; Biruck Woldai; Eyasu Habte; Mulugeta Russom (BMC, 2019)
Abstract Background Although over the counter (OTC) drugs are believed to be relatively safe, their inappropriate use could have serious implications. The aim of the study was to assess the practice of self-medication, prevalence of risky practice and its associated factors in pharmacy outlets of Asmara, Eritrea. Methods A descriptive cross-sectional study was conducted among 609 customers in 20 pharmacy outlets in Asmara between August and September, 2017. Two-stage cluster sampling was employed and data were collected using a structured questionnaire through face to face exit interviews. Descriptive statistics and multivariate logistic regression were performed using SPSS (version 22). Results Of the 609 customers, 93.7% had practiced self-medication with OTC drugs; of which 81.8% were at risky practice. On average, each participant was using OTC drugs at least once a month (Median = 1, IQR = 3.67). Educational level (p < 0.0001), religion (p = 0.047), occupation (p = 0.027) and knowledge regarding OTC drugs (p = 0.019) were significantly associated with risky practice. Respondents with elementary and below educational level were fifteen times (AOR = 15.49, CI: 1.97, 121.80) at higher risk compared to those with higher education, and students were almost three times (AOR = 2.96, CI: 1.13, 7.73) at higher risk than governmental employees. Furthermore, respondents with below average score in knowledge were more likely to be engaged in risky practice (AOR = 1.83, CI: 1.11, 3.04) compared to those with above average score. The most frequently preferred OTC drug group was analgesics (34.3%) followed by antipyretics (15.7%) and cough and cold preparations (14.2%). About 14% of the respondents admitted that they had taken more than the recommended dose and 6.9% had experienced drug related problems following the consumption of OTC drugs. Always, 35% of the respondents read package insert(s) and 73.9% check expiry dates while purchasing OTC drugs. Refrigerating OTC drugs, where it is not recommended, was also one of the prominent risky practices. Conclusions This study revealed that inappropriate self-medication practice with OTC drugs was prevalent requiring early intervention to minimize the risks.